Versatile time-cost algorithm (VTCA) for scheduling non-preemptive tasks of time critical workflows in cloud computing systems. (1st January 2013) - Babu, L.D. Dhinesh; Krishna, P. Venkata
In cloud computing environments, resources and infrastructure are provided as a service over internet on demand. The users are interested in reducing the service cost provided by the cloud service providers. Scheduling tasks of workflows play a vital role in determining performance of cloud computing systems. Workflows have many tasks in it and are interdependent on each other. Time critical workflows comprise of a collection of tasks which should be completed as early as possible so that other workflows get its turn. The budget involved in executing the time critical tasks is very high. The execution cost increases whenever we try to reduce the execution time. In this paper, we propose a method called versatile time-cost algorithm (VTCA) to schedule time critical workflows with minimum cost. VTCA will schedule the tasks to complete in earliest possible time as well as optimise the cost involved in resource provisioning. The results of experiments conducted using CloudSim simulator show that our scheduling policy minimises the completion time of workflows than other existing algorithms like min-min and fair max-min by 5% to 30% and it also reduces the costs by 5% to 35%.